3-Hydroxy-3-Methylglutaryl-Coenzyme A Reductase Inhibitors Attenuate β-Amyloid-Induced Microglial Inflammatory Responses - Cordle, Andrew (J Neurosci, 2005)
Alzheimer's disease (AD) is characterized by extracellular deposits of fibrillar β-amyloid (Aβ) in the brain, a fulminant microglial-mediated inflammatory reaction, and neuronal death. The use of 3-hydroxy-3-methylglutaryl-coenzyme A reductase inhibitors (statins) is associated with a reduced risk of AD, which has been attributed to the cholesterol-lowering actions of these drugs. Statins have been reported recently to have anti-inflammatory actions in addition to their classic lipid-lowering effects. We report that statins robustly inhibited the Aβ-stimulated expression of interleukin-1β and inducible nitric oxide synthase and the production of nitric oxide by microglia and monocytes. Statin treatment also blocked the rac1-dependent activation of NADPH oxidase and superoxide production. The anti-inflammatory actions of the statins were attributable to their ability to reduce the levels of isoprenyl intermediates in the cholesterol biosynthetic pathway. The effect of statins could not be reversed by exogenous cholesterol supplementation, indicating that the anti-inflammatory actions are distinct from their cholesterol-lowering actions. The addition of the isoprenyl precursors, mevalonic acid, and geranylgeranyl pyrophosphate (GGpp) attenuated the statin-mediated downregulation of inflammatory markers. Prevention of protein isoprenylation by the GGpp transferase inhibitor (GGTI-286) or inhibition of Rho-family function with Clostridium difficile Toxin A blocked the inflammatory response similar to the effect of statin treatment. We argue that the statin-mediated decrease in AD risk arises from their pleiotropic actions, effecting a reduction in neuronal Aβ production and microglia-directed inflammation.